GAMBARAN PERENCANAAN KARIR SISWA YANG AKTIF BERORGANISASI DI SMA N 1 KARANGANYA - Nanda Aryanti Ashari; Heris Hendriana; Ecep Supriatna (IKIP Siliwangi, 2020)
The purpose of this study is to describe the career planning of students who are active in organizations in SMA N 1 Karanganyar. This research uses descriptive quantitative method. Data collection in this study was obtained from giving questionnaires to 35 students who were active in organizations. The results obtained from this study indicate that students who are active in organizations have a picture of a mature career planning, the results of the questionnaire data processing show that 86% are in the high category and 14% are in the medium category.Keywords: : Career Planning, Students Active in Organizing